Impact of climate change on wheat security through an alternate host of stripe rust. (29th December 2021) - Zhang, Nannan; Liao, Ziyan; Wu, Shuang; Nobis, Michael Peter; Wang, Jinniu; Wu, Ning
Abstract: In the 21st century, stripe rust, caused by Puccinia striiformis f. sp. tritici ( Pst ), is still the most devastating disease of wheat globally. Despite the critical roles of the alternate host plants, the Berberis species, in the sexual reproduction and spread of Pst, the climate change impacts on the redistribution of Berberis plants, and their potential risk of incurring wheat stripe rust are scarcely discussed in the literature. This study evaluated the potential risk of Pst in wheat cultivation in Sichuan Province, China, for the first time, by analyzing the dynamics of Berberis plants and the change in Pst oversummering range under climate change scenarios. Ensembles of small models (ESMs) in combination with four algorithms were used to project the future (i.e., 2041–2060, 2061–2080, and 2081–2100) distributions of 54 Berberis species in Sichuan Province based on two shared socioeconomic pathways (SSP) scenarios. The species richness of Berberis was predicted to increase in northwestern Sichuan but decreased in southern and eastern Sichuan under both SSP245 and SSP585 scenarios. The mean temperature of the driest quarter was found to be the determinant of the distributional shifts for the majority of Berberis plants. Our overlapping assessments indicated that the risk of wheat stripe rust would be reduced in southwestern Sichuan. In contrast, it would be aggravated in the northwest due to the predicted shifts of Berberis plants northwards and stronger shrinkage of Pst oversummering range occurring in the south than in the north. In the "hotspots" of the stripe rust pathogen, risk assessment in advance could provide a scientific basis for decision‐makers and local communities in effectively controlling wheat stripe rust, thus further sustaining food security through adapting to future climate change. Abstract : This study, for the first time, evaluated the potential risk of Pst on wheat cultivation in Sichuan Province, China comprehensively through analyzing the dynamics of Berberis plants and the change of Pst over‐summering range under climate change scenarios. Our overlapping assessments indicated that the risk of wheat stripe rust would be reduced in southwestern Sichuan while aggraded in the northwest due to the predicted shifts of Berberis plants northwards and stronger shrinkage of Pst over‐summering range occurring in the south than in the north.